New firm formation by industry over space and time: a multi-level analysis for Germany - Michael Fritsch; Oliver Falck (European Regional Science Association (ERSA), 2002)
We apply a multi-level approach to analyze the effect of three groups of determinants on new firm formation simultaneously: industry, location and changes over time. The data are for West Germany and cover the 1983-97 period. Our analysis indicates, that innovation activities and the technological regime play a significant role for new firm formation processes. There are also considerable differences with regard to the impact of a number of variables on startups between manufacturing and the service sector. Changes in demand are conducive for new firm formation while a high level of unemployment in a region obviously makes a relatively uncomfortable environment for start-ups. JEL classification: D21, L10, R10 Keywords: New firm formation, industrial economics, regional economics, entrepreneurship.
Keywords: 330